Penerapan Starbo-AFE untuk Produksi Kompos Kelompok Tani Giri Mukti Kabupaten Sarolangun: Implementation of Starbo-AFE for Compost Production by the Giri Mukti Farmers Group in Sarolangun Regency - Adriani, Adriani; Lestari, Ardiyaningsih Puji; Fahmida, Fahmida (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2026)
This community service program aims to improve partners’ knowledge and skills in composting using Starbo-AFE. Partners’ problems are limited raw materials for composting and the slowness of the composting process. Therefore, it is necessary to disseminate compost processing technology using Starbo-AFE. This activity is carried out in 5 stages: socialization, training, application of the Starbo-AFE technology, assistance with production equipment, and mentoring and evaluation. The socialization activity began with a discussion with farmer groups, PPL, and village officials to determine the action plan. The training was attended by 30 people, who received technical materials on composting and the use of Starbo-AFE as an activator. The technology is applied using the Starbo-AFE activator in compost production, with rice husks and chicken feces as compost materials. Mentoring and evaluation are carried out by implementing the agreed production process. The assessment results from the questionnaire indicate that partner perceptions were above 4, with a range of 4.23–4.69. This means the community service activity is well-suited to the group’s needs. This community service activity concludes that it has gone according to plan, from socialization and training to assistance with production support equipment and the compost production process.